Culture still matters : notes from the field - Varisco, Daniel Martin. (Social, Economic and Political Studies of the Middle East and Asia, 2018)
Varisco's Culture Still Matters: Notes from the Field is on the relationship between ethnographic fieldwork and the culture concept in the ongoing debate over the future of anthropology, drawing on the history of both concepts. Despite being the major social science that offers a methodology and tools to understand diverse cultures worldwide, scholars within and outside anthropology have attacked this field for all manner of sins, including fostering colonialism and essentializing others. This book revitalizes constructive debate of this vibrant field's history, methods and contributions, drawing on the author's ethnographic experience in Yemen. It covers complicated theoretical concepts about culture and their critiques in readable prose, accessible to students and interested social scientists in other fields. With forewords from Bryan S. Turner and Anouar Majid.